The concept of personal and professional empowerment of nurses - Stanisavljevic, Sanja; Kekus, Divna; Dimoski, Zvonko; Majstorovic, Biljana; Stojanovic, Dragica (Nursing in the 21st Century, 2012)
THE CONCEPT OF PERSONAL AND PROFESSIONAL EMPOWERMENT OF NURSESIntroduction. The response to the challenges of contemporary professional nursing practice in a time of intense social changes, scientific developments and multicultural environment requires a new quality of professional activities. In order to overcome the current decline in nursing profession, such as low competence for decision-making on the one hand and a high level requirements and high responsibilities on the other hand, the issue imposes the necessity of adopting the concept of personal and professional empowerment of nurses in the development and strengthening of professional identity and the preservation of professional autonomy.Aim. To show the importance of adopting the concept of personal and professional empowerment of nurses, as well as developing and implementing programs in this field.Methods: Descriptive analytical approach.Results. The work summarizes the most important elements of professional competence in nursing, stressing the importance of developing an incentive program for the development of social skills, self-concept (self-esteem, self-acknowledgement), interculturalism, and continuous professional development, in order to involve the nursing into contemporary science and social activities.Conclusions. With encouraging and investing in educational facilities of nursing profession the pre requirements have been created for an independent, versatile, competent, innovative and creative individuals to represent it. Professional identity of modern nursing could be built on foundations of broad social and professional skills, which is a prerequisite for serious work on building their own personality. The concept of personal and professional empowerment is the path to social, professional and moral development of nurses.